2014
DOI: 10.1111/jphs.12073
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study investigating the potential drug-drug interactions in internal medicine department, Alahsa, Saudi Arabia

Abstract: Objective The aim of this study was to identify the drug-related problems and drug-drug interactions (DDIs) among the inpatients admitted to an internal medicine ward. Method A prospective, exploratory study was planned and all the prescriptions of inpatients admitted to the internal medicine department from 10 to 24 April 2011 were assessed at a public hospital in Alahsa, Saudi Arabia. Descriptive analysis was performed for sociodemographic aspects of the patients. Prescriptions of the studied population were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
7
0
1
Order By: Relevance
“…Examples of serious drug interactions detected in this study are sertraline and buspirone, carbamazepine and clopidogrel, daclatasvir and sofosbuvir, aspirin and perindopril, aspirin and lisinopril, aspirin and captopril, carbamazepine and duloxetine, and amlodipine and simvastatin. The ratio of serious to significant drug interactions in this current study was 1:9 which was comparable to the results of another study [22] which reported that the serious (8.5%) to significant drug interactions (69%) ratio was 1:8. The rates of dosing and frequency of administration errors were 3.4% and 29%, respectively.…”
Section: Resultssupporting
confidence: 89%
“…Examples of serious drug interactions detected in this study are sertraline and buspirone, carbamazepine and clopidogrel, daclatasvir and sofosbuvir, aspirin and perindopril, aspirin and lisinopril, aspirin and captopril, carbamazepine and duloxetine, and amlodipine and simvastatin. The ratio of serious to significant drug interactions in this current study was 1:9 which was comparable to the results of another study [22] which reported that the serious (8.5%) to significant drug interactions (69%) ratio was 1:8. The rates of dosing and frequency of administration errors were 3.4% and 29%, respectively.…”
Section: Resultssupporting
confidence: 89%
“…43.4% prevalence rate for pDDIs was observed during the study in the cardiac patients at an Iranian hospital (Namazi, 2012). Few other studies also suggest that cardiac patients are at higher risk of pDDIs as a number of cardiac drugs are associated with pDDIs as these patients are more vulnerable to pDDIs due to complexity of disease and multiple drug therapy (Albadr et al, 2014, Smithburger et al, 2010, Straubhaar et al, 2006). Researchers have found that the drugs commonly involved in pDDIs include cardiac glycosides, NSAIDs, diuretics and calcium channel blockers (Queneau et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of the interactions previously described was PD in 33% of cases and PK in 67%; these rates were very similar to our results as shown in Table 2. Another study conducted by Albadr et al [24] concluded that 47 % of the detected DIs were PD and 53% were PK. This study used similar methodology, and the incidences of PK and PD interactions were similar to our results.…”
Section: Discussionmentioning
confidence: 95%